2017
DOI: 10.18632/oncotarget.20793
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphisms of ATG5 predict survival and recurrence in patients with early-stage esophageal squamous cell carcinoma

Abstract: Esophageal squamous cell carcinoma (ESCC) is a deadly disease with high risk of tumor recurrence even among patients with an early pathologic stage of tumor. In the current study, we investigate the association between 20 SNPs of the ATG5 gene and prognosis of patients with early-stage ESCC. A total of 305 patients diagnosed with early-stage ESCC were enrolled in the study and randomly assigned to a training set (n=93) or replication set (n=212). The genotypes of candidate SNPs (single nucleotide polymorphisms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 47 publications
0
22
0
Order By: Relevance
“…The utility of genes as biomarker has been demonstrated and a number of genes have been reported. In a work by Yang PW et al, increased ATG5 expression was observed in esophageal cancer compared with normal tissue [39]. His group also found higher ATG5 expression tumor group had worse prognosis including the overall survival (OS) and progression-free survival (PFS).…”
Section: Discussionmentioning
confidence: 95%
“…The utility of genes as biomarker has been demonstrated and a number of genes have been reported. In a work by Yang PW et al, increased ATG5 expression was observed in esophageal cancer compared with normal tissue [39]. His group also found higher ATG5 expression tumor group had worse prognosis including the overall survival (OS) and progression-free survival (PFS).…”
Section: Discussionmentioning
confidence: 95%
“…The results showed that esophageal cancer patients with lower expression of ATG5 had a longer overall survival (Figure 5F). Autophagy-related gene 5 (ATG5) is identified as an essential autophagy gene, contributing to the malignant phenotype of cancer cells, and its higher expression is closely associated with poor prognosis in patients with earlystage ESCC (6)(7)(8). However, the association between ATG5 and CDKL3 in cancer has not been studied previously.…”
Section: Gene Expression Profile Analysis Revealed Atg5 Was a Downstrmentioning
confidence: 99%
“…Autophagy is a cellular self-protection process by which it escapes from external stress via metabolizing intracellular proteins and organelles and serves an essential role in carcinogenesis and progression (4,5). ATG5 is identified as a critical autophagy gene, contributing to the malignant feature of cancer cells, and its higher expression predicts poor prognosis in patients with early-stage ESCC (6)(7)(8). However, the association between ATG5 and CDKL3 in cancer has not been studied previously.…”
Section: Introductionmentioning
confidence: 99%
“…The utility of genes as biomarker has been demonstrated and a number of genes have been reported. In a work by Yang PW et al [38] , increased ATG5 expression was observed in esophageal cancer compared with normal tissue. His group also found higher ATG5 expression tumor group had poorer prognosis including the overall survival (OS) and progression-free survival (PFS).…”
Section: Discussionmentioning
confidence: 95%